Present and future sturgeon and caviar production and marketing: A global market overview - Bronzi, P.; Rosenthal, H. (Journal of applied ichthyology, 2014)
Summary Continuous drastic declines in natural sturgeon populations over the past 30 years plus a high market demand for caviar have led the way for sturgeon farming, mainly for the production of caviar. Russia, Iran, members of the European Union, China and the USA were among the first; however, for the very same reasons countries outside the natural range of sturgeons also became involved (e.g. Uruguay, Arabian countries, Israel, and more recently Vietnam). At present (2012), the total caviar output from aquaculture is estimated at 260 tonnes, a production that could increase to 500–750 t within the next 10 years. If these figures are realistic, the future of caviar trade will be determined mainly by demand‐driven price structures, with the appearance of a new and evolving ‘mass market’ in addition to the traditional luxury high‐priced market. Other issues are the uncertainties and opportunities in the market place. All of these issues indicate that this relatively new branch of the aquaculture industry faces similar growing pains as in previous developments (e.g. salmon farming) but within a shorter time frame. The same drive that gave the incentive to farm sturgeons also provided, since the early 1970s, the incentives to seek alternative products that could fill the void in caviar supplies and even create new market sectors. The various products currently found on the market have been divided into six categories: (a) true caviar (using eggs from sturgeons); (b) substitute caviar (eggs derived from other fish species or from other animals); (c) imitation caviar (caviar‐like products constructed from other biological substances, imitating caviar in appearance and taste); (d) simulated caviar (produced by other biological substances to simulate only the taste of caviar, but not the appearance); (e) derivates (products that contain true caviar as a recipe component); (f) products with emotional associations to caviar (not related to caviar at all, but use the name as a marketing strategy to evoke a luxury image and infer a high value). At present, the eggs of more than 38 species of fish, besides sturgeons, and three species of other animals are used to produce substitutes. About 15 ‘caviar‐like’ preparations are used as raw materials – such as fish flesh, seaweed, and others mixtures. Five products can be considered simulations; few use caviar as a component in their production recipes. A variety of objects (unrelated to caviar) are currently marketed, but use ‘caviar’ in their trademark.